Predicting the no-reflow phenomenon following successful percutaneous coronary intervention. (June 2010) - Galiuto, L; Paraggio, L; Liuzzo, G; de Caterina, AR; Crea, F
In the setting of acute myocardial infarction, early and adequate reopening of an infarct-related artery is not necessarily followed by a complete restoration of myocardial perfusion. This condition is usually defined as 'no-reflow'. The pathophysiology of no-reflow is multifactorial since extravascular compression, microvascular vasoconstriction, embolization during percutaneous coronary intervention, and platelet and neutrophil aggregates are involved. In the clinical arena, angiographic findings and easily available clinical parameters can predict the risk of no-reflow. More recently, several studies have demonstrated that biomarkers, especially those related to the pathogenetic components of no-reflow, could also have a prognostic role in the prediction and in the full understanding of the multiple mechanisms of this phenomenon. Thus, in this article, we investigate the role of several biomarkers on admission in predicting the occurrence of no-reflow following successful percutaneous coronary intervention.